In Vitro Antioxidant Activities of Aqueous Extracts Derived from Leaves of Juvenile and Mature Shoots of Ficus pumila L. (Moraceae) - Tkachenko, Halyna; Buyun, Lyudmyla; Kurhaluk, Natalia; Honcharenko, Vitaliy; Prokopiv, Andriy; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The aim of this study was to investigate the in vitro antioxidant activity of aqueous extracts from the leaves developed on the shoots of various developmental stages (juvenile and mature/generative) of Ficus pumila L. using the oxidative stress biomarkers [2-thiobarbituric acid reactive substances (TBARS), carbonyl derivatives content of protein oxidative modification, total antioxidant capacity] on the equine erythrocytes’ suspension model. Freshly collected leaves were washed, weighed, crushed, and homogenized in 0.1M phosphate buffer (pH 7.4) (in proportion 1:19, w/w). The equine erythrocyte aliquots were used in the study. A volume of 0.1 ml of the F. pumila extract was added to 1.9 ml of clean equine erythrocytes. For positive control (blank), phosphate buffer was used. The treatment with the extract obtained from leaves of mature shoots reduced the erythrocytes TBARS level by 22 % (p=0.029), while TBARS level was increased by 15.5 % (p>0.05) when incubated with an extract derived from leaves of juvenile shoots as compared to untreated erythrocytes. When equine erythrocytes were incubated with extract obtained from leaves of mature shoots, the ketonic derivatives level was significantly decreased by 6.9 % (p=0.040), while non-significantly decrease both aldehydic and ketonic derivatives of OMP was observed after incubation with extract derived from juvenile shoots (by 8.18 and 12.5 %, p>0.05). The treatment by F. pumila leaf extract (from juvenile and mature shoots) caused the increase of TAC in erythrocyte suspension as compared to untreated erythrocytes. Thus, extracts derived from both juvenile and mature shoots resulted in an increase of total antioxidant capacity of equine erythrocytes’ suspension.